A Cheiloscopic Study On Diabetes Mellitus Type-2 Patients With Reference To Deha Prakruti (Body Constitution). - Dr.Chaitra.S; Dr.Poornima Jalawadi; Dr.Shelly Divyadarshan (Revista Electronica de Veterinaria, 2024)
Introduction: Diabetes mellitus (DM) is a global disease, and the prevalence is increasing particularly in developing countries. It represents a major threat of the public health condition worldwide. According to AYURVEDA, Prakruti Pareeksha(Examination of Body Constitution)  is one of the prime parameter for examination of body and also held at high esteem when it comes to diagnosis of diseases. So based on the information gathered through Prakruti Pareeksha and Cheiloscopy, an effort is made to PREVENT the incidences of Diabetes Mellitus.Methodology: A study was conducted among previously diagnosed 50 Type 2 Diabetes mellitus patients from various hospitals, Mysuru. The prakruthi is assessed using Quesstionare. Lip prints were collected and analyzed with prakruti.Results: As per the observations it is found that the out of 50 samples majority of Pitta-kaphaja prakruthi (36%) individuals and also predominance with Reticular (27%) and complete straight (26%) pattern of lip prints  are more prone to Type 2 Diabetes Mellitus.Conclusion: Diabetes mellitus (DM) is a global disease, and the prevalence is increasing particularly in developing countries.Prakriti Pareeksha is one of the prime parameter for examination of body and also held at high esteem when it comes to diagnosis of diseases. This is a pilot study with 50 samples there is further lot of scope for study towards achievement of accuracy with bigger sample data and considering various other Cheiloscopic criteria.